Peran Penyuluh Pertanian dalam Meningkatkan Pendapatan Usahatani Jagung di Desa Longalo - Ersa Abdullah; Irwan Bempah; Ramlan Mustafa (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The presence of agricultural extension workers in Longalo Village is considered crucial in increasing farmers' income. These extension workers are highly needed to assist farmers in addressing their challenges and to help enhance corn production, which can yield profits. They serve as educators, facilitators, motivators, and consultants. This research aims to analyze the role of agricultural extension workers in improving income from corn farming in Longalo Village. This research was conducted in Longalo Village for 2 months, from August to October 2023. The number of respondents consisted of 71 farmers out of a population of 242, determined using the Slovin formula for sample selection. The data analysis employed in this research was quantitative descriptive analysis. The research findings indicate that the role of agricultural extension workers in improving farm income, in their capacities as educators, facilitators, motivators, and consultants, falls within the category of actively contributing, with a percentage of 78.59%.